An analysis of Cambodia's policy-maker's acceptance of renewable and nuclear energy. Issue 1 (4th March 2022) - Kim, Soohyeon; Cho, Inkyung; Oh, Surim; Heo, Eunnyeong
ABSTRACT: In recent years, the Cambodian government has been promoting clean energy sources, making it essential to understand better the entry/barrier conditions for greater utilisation of renewable and nuclear power. Accordingly, this study aims to analyse the potential for expanding renewable and nuclear energy use in Cambodia. To derive practical recommendations for the political sector, we surveyed officials from the government and various institutions. Specifically, we measured Cambodia's acceptance of renewable and nuclear energy, derived entry/barrier conditions, and identified the decision-making priorities of the government in introducing and expanding each energy source. The analysis employed the ordered logit-probit analysis and analytic hierarchy process (AHP). This study provides a practical guide for the Cambodian government, and investors and partners who intend to contribute to the renewable and nuclear systems of the country: renewable energy requires strategies maximising the economic benefits of its rich potential; while nuclear generation needs broad economic and technological cooperation with foreign governments and companies, and preparation for socio-political instability.